BCG-INDUCED PRO-INFLAMMATORY PHENOTYPE OF MESENCHYMAL STEM CELLS: EFFECT OF IMMUNE MODULATORS - A. Sh. Shvarts; S. N. Belogorodtsev; A. E. Petrenko; L. O. Degtyareva; A. I. Shakhmuradova (Туберкулез и болезни лёгких)
In case of mycobacterial infection the granulomatous infiltration foci contain the significant amount of mesenchymal stem cells (MSC), which functional phenotype and respective function in anti-tuberculosis immune defense remain unknown.Goal of the study: to characterize the MSC phenotype, formed by their interaction with BCG of M. bovis and to evaluate the changes in this phenotype caused by the action of inhibitors and stimulants of immune regulatory action.Materials and methods: MSC retrieved from bone marrow of mice were cultured with the presence and absence of BCG of M. bovis and/or poludanum TLR3 agonist; and the effect of two latter on the production of pro- and anti-inflammatory cytokines was evaluated by enzyme multiplied immunoassay. Flow cytometry and radioactive testing were used to evaluate the impact of cultured BCG fluid and poludanum-conditioned MSC on the proliferative and apoptotic activity of splenocytes. The inhibitors of indoleamine 2,3-dioxygenase (IDO), cyclooxygenase-2 (COG-2) or NO synthase were added to certain cultures alone with BCG and poludanum, and the contributions of IDO, COG-2 and NO to BCG and poludanum-induced response were assessed.Results. Pro-inflammatory polarization of MSC under the action of BCG and poludanum was demonstrated. Pro-inflammatory MSC phenotype correlated to their anti-apoptogenic and growth-stimulating actions on the splenocytes. It was demonstrated that IDO and NO restrained BCG-induced polarization and conversely COG-2 promoted BCG-induced pro-inflammatory polarization of MSC.Conclusions. 1. MSC actively participate in the formation of immunologic anti-mycobacterial resistance. 2. Targeted regulation of IDO and NO production can be feasibly applied for formation of anti-tuberculous vaccinal immunity and control mycobacterial infection.